The Effect of Block Grants on the Level of Community Welfare Through Education Function Expenditure - Aqilla Cinantya Wara Dayinta; Agus Suman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research is motivated by the high transfer funds (DAU and DBH) and the high expenditure on education functions in East Java. The high transfer funds and education function expenditure have not been able to make East Java have a high HDI compared to other regions in Java. Therefore, this study aims to determine the effect of DAU and DBH on HDI through education function expenditure in cities and districts in East Java Province in 2018-2022. The data in this study are panel data sourced from the APBD realisation data of 29 districts and 9 in East Java Province published by the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance. The research uses path analysis technique with the results of DAU has a significant positive effect on education function expenditure, DBH has no effect on education function expenditure, DAU has a significant negative effect on HDI, DBH has a significant positive effect on HDI, education function expenditure has no effect on HDI, DAU has no effect on HDI through education function expenditure, and DBH has no effect on HDI through education function expenditure.